(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
The development of technology has made learning English faster, easier, more interesting, and more convenient. This article explores the impact of digital tools, multimedia resources, artificial intelligence, and online platforms in improving English language proficiency. It also discusses the benefits and challenges of integrating technology into English language instruction.